Association between sociodemographic characteristics and adherence to early detection of breast cancer - Rosy Denyse Pinheiro de Oliveira; Iarlla Silva Ferreira; Régia Christina Moura Barbosa Castro; Ana Fátima Carvalho Fernandes (Universidade Federal do Ceará, 2022)
Objective: to verify the association between sociodemographic characteristics and the performance of actions for early detection of breast cancer. Methods: a cross-sectional study was carried out in six primary health care units, with 400 women considered a target population for actions for early detection of breast cancer. The Chi-square test of independence (2x2) was used for inferential analysis. Results: most women were between 60 and 64 years old, married, had low education and lacked an occupation or health insurance. A significant association was found between marital status and the interval between requesting and performing a mammogram (X2(1) = 208.185, p<0.001, Phi-coefficient= 0.902; Confidence Interval: 0.0308-0.0928). Women without a partner had a 0.95 times higher prevalence of having a mammogram. Conclusion: there was an association between the sociodemographic variable marital status and the performance of mammography in a shorter period, and not having a partner was a protective factor. Contributions to practice: the elucidation of factors related to the performance of actions for breast cancer screening can signal patients who need greater vigilance regarding the presence of signs and symptoms suggestive of breast cancer.